PENGARUH PEMBERIAN JAHE MERAH TERHADAP PENCEGAHAN HIPER EMESIS GRAVIDARUM PADA IBU HAMIL - Hernawati, Yeti; sumiati, eli (Jurnal Sehat Masada, 2025)
In Indonesia there are 50-75% cases of nausea and vomiting experienced by pregnant women in the first trimester or early in pregnancy. Emesis if not treated immediately will increase to hyperemesis and can result in impaired fetal growth, the fetus dies in the womb and the fetus can experience congenital abnormalities. Overcoming nausea and vomiting during pregnancy can be done through pharmacological and non-pharmacological measures. The purpose of this research is to determine the effect of ginger candy (Zingiber Officinale) on the frequency of emesis gravidarum in pregnant women in the Working Area of the Sukaresmi Public Health Center, Cianjur Regency, in 2023. The method used in this study was a Quasi Experimental Design research method with a Post-test Only Control Group Design approach which consisted of an experimental class, namely pregnant women who experienced emesis gravidarum were given ginger candy, while in the control class pregnant women who experienced emesis gravidarum were given candy containing contains no ginger or placebo. Sampling was done by accidental sampling. The sample taken was 62 respondents who were divided into 2 groups, namely 31 intervention groups and 31 control groups. Ginger candy was given to the intervention group while the control group was given sugar candy. The statistical test results, it was found that p value = 0.000 (p value ≤ 0.05) meaning that there was a significant influence between giving ginger candy (Zingiber officinale) on reducing emesis gravidarum in pregnant women in the working area of the Sukaresmi Health Center, Cianjur Regency, in 2023. The conclusion in this study is that there is an effect of giving ginger candy on emesis gravidarum in pregnant women in the Working Area of the Sukaresmi Public Health Center, Cianjur Regency, West Java in 2023.